Stabilization of tryptophan hydroxylase 2 by l‐phenylalanine‐induced dimerization. Issue 10 (22nd August 2016) - Tidemand, Kasper D.; Christensen, Hans E. M.; Hoeck, Niclas; Harris, Pernille; Boesen, Jane; Peters, Günther H.
Abstract : Tryptophan hydroxylase 2 (TPH2) catalyses the initial and rate‐limiting step in the biosynthesis of serotonin, which is associated with a variety of disorders such as depression, obsessive compulsive disorder, and schizophrenia. Full‐length TPH2 is poorly characterized due to low purification quantities caused by its inherent instability. Three truncated variants of human TPH2 (rc h TPH2; regulatory and catalytic domain, NΔ47‐rc h TPH2; truncation of 47 residues in the N terminus of rc h TPH2, and c h TPH2; catalytic domain) were expressed, purified, and examined for changes in transition temperature, inactivation rate, and oligomeric state. c h TPH2 displayed 14‐ and 11‐fold higher half‐lives compared to rc h TPH2 and NΔ47‐rc h TPH2, respectively. Differential scanning calorimetry experiments demonstrated that this is caused by premature unfolding of the less stable regulatory domain. By differential scanning fluorimetry, the unfolding transitions of rc h TPH2 and NΔ47‐rc h TPH2 are found to shift from polyphasic to apparent two‐state by the addition ofl ‐Trp orl ‐Phe. Analytical gel filtration revealed that rc h TPH2 and NΔ47‐rc h TPH2 reside in a monomer–dimer equilibrium which is significantly shifted toward dimer in the presence ofl ‐Phe. The dimerizing effect induced byl ‐Phe is accompanied by a stabilizing effect, which resulted in a threefold increase in half‐lives of rc h TPH2 and NΔ47‐rc h TPH2. Addition ofl ‐Phe to the purification buffer significantly increases the purification yields, which will facilitate characterization of h TPH2. Abstract : Tryptophan Hydroxylase 2 (TPH2) is expressed in the central nervous system and catalyses the rate‐limiting step in the biosynthesis of serotonin. TPH2 has a regulatory domain but little is known about its role. We show that this domain is involved in the dimerization of TPH2 and that L‐Phe can induce a thermostable dimer of TPH2 variants.